Peristeen® transanal irrigation in paediatric patients with anorectal malformations and spinal cord lesions: a multicentre Italian study. (January 2016) - Midrio, P.; Mosiello, G.; Ausili, E.; Gamba, P.; Marte, A.; Lombardi, L.; Iacobelli, B. D.; Caponcelli, E.; Marrello, S.; Meroni, M.; Brisighelli, G.; Leva, E.; et al.
Abstract: Aim: In paediatric and adult patients with neurogenic bowel, transanal irrigation (TAI) of the colon has gained popularity due to the introduction of a specifically designed device. The aim of this pilot study was to present the results of TAI using the Peristeen ® TAI system in a group of paediatric patients with anorectal malformation (ARM) and congenital or acquired spinal cord lesions (SCLs). Method: Eight Italian paediatric surgery and spina bifida centres participated in the study. The inclusion criteria were age between 6 and 17 years, weight above 20 kg and unsatisfactory bowel management. Patients with chronic inflammatory bowel disease, mental disability and surgery within the previous 3 months were excluded. At the beginning of treatment (T0) and after 3 months (T1) the Bristol scale, a questionnaire assessing bowel function, and two questionnaires on quality of life (QoL) for patients aged 6–11 years (CHQ‐pf50) and 12–17 years (SF36) were administered. Results: Eighty‐three patients were enrolled, and seventy‐eight completed the study (41 ARMs, 37 SCLs). At T1, constipation was reduced in ARMs from 69% to 25.6% and in SCLs from 92.7% to 41.5%, faecal incontinence in ARMs from 50% to 18.6% and in SCLs from 39% to 9.8% and flatus incontinence in ARMs from 20.9% to 9.8% and in SCLs from 31.7% to 10%. At T0, the Bristol Stool Scale types were 1–2 in 45% of ARMs and 77.5% of SCL patients, whereas at T1 types 1–2 were recorded in only 2.5% of SCL patients. QoL improved in both groups. In the younger group, a significant improvement in QoL was recorded in ARM patients for eight of nine variables and in SCL patients for seven of nine variables. Conclusion: This study showed that Peristeen TAI resulted in a significant time reduction in colonic cleansing, increased independence from the carer and improved QoL in paediatric patients with ARMs and SCLs.